Author Correction: Novel hybrid method to additively manufacture denser graphite structures using Binder Jetting (Scientific Reports, (2021), 11, 1, (2438), 10.1038/s41598-021-81861-w) - Popov, Vladimir; Fleisher, Alexander; Muller‑Kamskii, Gary; Avraham, Shaul; Shishkin, Andrei; Katz‑Demyanetz, Alexander; Travitzky, Nahum; Yacobi, Yair; Goel, Saurav (Scientific Reports, 2022)
Firstly, Shaul Avraham and Yair Yacobi were omitted from the author list in the original version of this Article.
CRIS-Team Scopus Importer:2022-02-04